Luminescence of copper-doped α-quartz crystal after oxygen treatment - A. Trukhin (Optical Materials: X)
Treatment of copper-doped natural α-quartz in oxygen atmosphere at 1200 °C leads to changes in luminescence properties. The luminescence center of AlO4−-Cu+ is modified. The intensity is low in the annealed sample and increases after X-ray irradiation at 293 K. Annealing of the irradiated sample leads to a strong peak of thermally stimulated luminescence (TSL) at ∼500 K. Its spectral composition is mainly due to the AlO4−-Cu+ center. Irradiation of the sample treated with oxygen at 77 K gives a new TSL peak at ∼180 K and a peak at 244 K existing in the untreated sample. Both peaks were attributed to Cuo centers released from different sites and recombined with a hole in AlO4 having additional oxygen. The introduction of copper ions into quartz removes alkali metal ions and eliminates the corresponding luminescence, but after treatment in oxygen, luminescence with similar parameters is restored at low temperatures. In this case, only the glow of the AlO4−-Cu+ center is observed in the recombination luminescence (TSL and afterglow). Therefore, modification of the AlO4−-Cu + center with oxygen imparts to this center properties similar to the complex center AlO4− (K, Na or Li ion) with monovalent aluminum ions, although the alkali ions are replaced by copper ions. The oxygen-treated sample exhibits an increased efficiency of energy transfer by excitons to the luminescence center, measured as excitation spectra in the region of fundamental absorption of silicon dioxide. The X-ray excitation of the self-trapped exciton luminescence does not depend on oxygen treatment. Also, the spectra of intrinsic optical reflection and Raman scattering do not change compared to the untreated sample. The obtained result is interpreted as a modification of the defect by high-temperature treatment in oxygen.